The study of mindfulness as an intervening factor for enhanced psychological well-being in building the level of resilience - Oh, Vincent Kim Seng; Sarwar, Abdullah; Pervez, Niaz (Frontiers in Psychology, 2022)
Background By using a practice like mindfulness, people may become more adaptable and flexible in difficult situations, which lowers the levels of unfavorable experiences. Only a small number of research have examined the connection between mindfulness and resilience, with mindfulness as a source of PWB influencing millennials’ resilience when faced with adversity. This study sought to close this gap by exploring the role that mindfulness practice plays in millennials’ PWB and subsequent increases in resilience to adversity. Methods In this study, key components linked to mindfulness, PWB, and resilience are combined with a thorough literature assessment. Millennials who are active members of the Ti-Ratana Youth in Malaysia and the Buddhist Missionary Society of Malaysia (BMSM) Youth Section make up the study’s sample population. Before completing the online survey form, each participant was instructed to engage in 4 weeks of supervised mindfulness practice. To assure the validity of the data gathered, it was crucial to secure the youth’s commitment. Only 231 of the 300 respondents who received the link to the online survey had replies that could be used for further research. To analyze the collected data and conduct hypothesis testing, Smart-PLS was used. Results Academic research has shown that factors, such as a heavy workload, time constraints, lengthy workdays, work-related home conflicts, and an unstable and uncertain environment all lead to a drop in PWB. According to the findings, the two most significant variables promoting resilience are mindfulness and positive PWB. The outcomes of this experimental study confirmed earlier findings that millennials’ PWB and resilience are enhanced by mindfulness training. Conclusion The study’s findings suggest that, in times of high uncertainty, mindfulness-based intervention programs should be expanded to include all young people. This study offers empirical support for the effectiveness of mindfulness-based interventions in raising PWB and resilience.